Efficient Arbitrage Under Financial Indexation : The Case of Chile - Mendoza, Enrique (Washington, D.C. : International Monetary Fund, 1991)
Legal restrictions governing financial transactions in Chile have produced a system in which most financial assets are either 30-day non-indexed assets or 90-day indexed assets. This paper analyzes data on the rates of return of these assets to determine the extent to which efficient arbitrage takes place under conditions of partial financial indexation. The data cannot reject the joint hypothesis that participants in financial markets formulate their expectations rationally and that these markets operate efficiently. The data also shows that the indexed/non-indexed interest spread is an accurate predictor of future changes in inflation. The significant implications of these findings for the conduct of monetary policy are also discussed in some detail.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Financial System; Indexation Mechanism; Inflation Rate; Inflation Risk; WP; Chile